1995
DOI: 10.3109/02656739509022460
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microregional perfusion, oxygenation, ATP and lactate distribution in subcutaneous rat tumours upon water-filtered IR-A hyperthermia

Abstract: The effect of hyperthermia on microcirculatory and metabolic parameters in s.c. DS-sarcomas of different sizes on the hind foot dorsum of SD-rats was investigated. Hyperthermia was carried out using a novel water-filtered, infrared-A radiation technique. Heating was performed at a rate of 0.5 degrees C/min until 44 degrees C was achieved in the tumour centre, which was maintained for 60 min. Using a multichannel laser Doppler flowmeter, red blood cell flux could be assessed continuously and at several sites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
4
41
0
1
Order By: Relevance
“…In the literature, HT has been reported to have distinctly heterogeneous effects on tumour blood flow, whereby this variability may be at least partially explained by the use of different heating protocols in tumours with different histologies. In the DS-sarcoma used in the present study, HT has previously been shown to have a bimodal effect on tumour blood flow with an initial increase in perfusion of up to 20% being followed by a decrease down to 25% of pretreatment values (Kelleher et al, 1995). Microvascular damage, which in some instances can even result in blood flow stasis, has frequently been seen following PDT (Reed et al, 1988;Fingar et al, 2000;Dolmans et al, 2002).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…In the literature, HT has been reported to have distinctly heterogeneous effects on tumour blood flow, whereby this variability may be at least partially explained by the use of different heating protocols in tumours with different histologies. In the DS-sarcoma used in the present study, HT has previously been shown to have a bimodal effect on tumour blood flow with an initial increase in perfusion of up to 20% being followed by a decrease down to 25% of pretreatment values (Kelleher et al, 1995). Microvascular damage, which in some instances can even result in blood flow stasis, has frequently been seen following PDT (Reed et al, 1988;Fingar et al, 2000;Dolmans et al, 2002).…”
Section: Resultsmentioning
confidence: 56%
“…Other potential factors that might be involved in the pronounced potentiation of the antitumour effects seen are a concerted action of PDT and HT on certain proteins or supramolecular structures (Prinsze et al, 1991) or a conversion of PDT-induced repairable lesions to irreparable lesions upon HT treatment (Chen et al, 2001). Additionally, increased lactic acid formation during HT, as has already been reported for this tumour model (Kelleher et al, 1995), may also result in a lower pH in tumour tissue, and since acidosis has been found to enhance the efficacy of ALA-PDT in vitro (Wyld et al, 1998), such metabolic changes within the tumour tissue may play a role in the effects of ALA-PDT þ HT.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Details of this method have been described earlier by Kelleher et al (1995Kelleher et al ( , 1998b. This method uses the Doppler shift (i.e.…”
Section: Laser Doppler Flowmetrymentioning
confidence: 99%